1988
DOI: 10.1136/jcp.41.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic colitis: detection of verotoxin producing Escherichia coli O157 in a clinical microbiology laboratory.

Abstract: SUMMARY Faeces (n = 1319) were examined over three months for the presence of non-sorbitol fermenting, verotoxin producing Escherichia coli (serotype 0157). Seven isolates were found, four from patients with bloodstained diarrhoea and three from patients with no evidence of blood in the faeces. Screening of all faecal samples with specific 0157 antiserum for non-sorbitol fermenting organisms and agglutination was an important adjunct to clinical and microscopic findings and helped detect cases of verotoxin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…DISCUSSION VTEC were not isolated in patients with IBD included in this study in contrast to the previously reported evidence suggesting that these organisms may have an aetiological role [9]. The failure to detect VTEC in other patient groups supports published data that they cause under 2 % of gastroenteritis in the UK [14]. It is possible that some cases could have been missed, as the rate of detection of VTEC in stools falls dramatically after the first few days of infection [15], and the VT property in E. coli 0 2.…”
Section: Resultssupporting
confidence: 72%
“…DISCUSSION VTEC were not isolated in patients with IBD included in this study in contrast to the previously reported evidence suggesting that these organisms may have an aetiological role [9]. The failure to detect VTEC in other patient groups supports published data that they cause under 2 % of gastroenteritis in the UK [14]. It is possible that some cases could have been missed, as the rate of detection of VTEC in stools falls dramatically after the first few days of infection [15], and the VT property in E. coli 0 2.…”
Section: Resultssupporting
confidence: 72%
“…The incidence of VTEC infections has not yet been extensively studied in Europe. Only in the UK has the role of VTEC been evaluated in hemorrhagic colitis (4), hemolytic uremic syndrome (5) and diarrhea (6). Outbreaks of hemorrhagic colitis and hemolytic uremic syndrome have also been reported in the UK (7,8).…”
Section: Vtec Was Comparable To That For Shigella Sppmentioning
confidence: 97%
“…Both types of shiga-toxic factors, Shiga-like toxin I and Shiga-like toxin II, killing both Vero and HeLa cells, induce fluid accumulation in ligated rabbit intestinal loops, and are lethal for mice and rabbits (5,6,7,8,9,10). Both toxic factors differ antigenically as well as with respect to their biological effect.…”
Section: Introductionmentioning
confidence: 99%